Unchecked Man’s Devious Will: US Age of Common Man and Gilded Age Versus Recent Iraq - M. Jamil, Dr. Adil (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: Bewildered by the wave of terror and on-going political corruption in Iraq, one feels compelled to dig deeper into the history of prosperous nations in an attempt to help eliminate the loss of time and human souls. In this endeavour, the study finds out that the current bleak circumstances in Iraq look in so many ways like the bloody events and widespread corruption during the 19th Century in the States, specifically in the Age of Common Man and the Gilded Age. Bleak ages, were eventually followed by a culture of peace and time of order and prosperity in the States.